Gallstone Ileus: Report Of Three Cases And Review Of Literature - Woo, Woo Sze Yao (British Journal Of Surgical Science, 2022)
Gallstone ileus (GI) is an uncommon sequela of cholelithiasis or gallbladder stones. It accounts for about 0.3-0.5% of incidences of cholelithiasis (1). In the same vein, it is also a rare etiology of intestinal obstruction. Approximately 1-4% of cases of intestinal obstruction are due to GI ( 2). However, we have encountered a series of cases of GI. Hence the question begs: Is GI a rare disease as reported in the medical literature or the spate of cases at our center was merely a statistical outlier attributable to external factors?